Guided bone regeneration in periodontology: review - Nadhia A. Harsas; Antonius Irwan (Makassar Dental Journal, 2018)
Alveolar bone loss caused by periodontal diseases is one of complication in periodontology. In some cases, alveolar bone loss is often followed by extraction as the treatment choice and resulting in large bone defects. Deficiency of bone volume and dimension can make difficulties on implant placement in the future. Guided bone regeneration is one of treatment modalities to create bone regeneration usually in edentulous area. The success of bone regeneration in large bone defects needs bone graft and barrier membrane material. There are various types of bone graft that can be used such as autograft, xenograft, allograft, alloplast, and bioglass. The rationale of GBR advocates mechanical exclusion of undesirable soft tissues from growing into the osseous defect, therefore barrier membrane plays an important role in GBR. Various types of materials have been developed, which can be grouped together as either non-resorbable or resorbable membranes. This paper reviews the uses of GBR especially in periodontology as one of therapeutic treatment choices for bone regeneration.